Simulation of collapse failure process of rock slope based on the smoothed particle hydrodynamics method - Zhang, Xiaoqiang; Song, Xiong; Wu, Shunchuan (Frontiers in Earth Science, 2023)
Limit equilibrium method (LEMs) or finite element method (FEM) for slope problems most frequently focus on the stability analysis. There are, however, still some problems for damage and failure evolution of rock slope with the LEMs or FEM because of the distortion of mesh. In this work, a mesh free particle approach named smoothed particle hydrodynamics (SPH) method is presented and is improved to analyze the damage and failure process of rock slope. In order to better describe the cause and mechanism of brittle failure for rock slope, the plastic factor was proposed and introduced into the SPH algorithm, and the conservation equations of SPH for brittleness characteristics was obtained. Based on the variation of displacement and time, an effective criteria was proposed to define the factor of safety in SPH simulation. And the Drucker-Prager Mohr-Coulomb strength criterion was implemented into the SPH algorithm to describe the elastic plastic behavior. Then three rock slope model with different precast cracks was analyzed to illustrate the performance of the proposed method. It is showed that the proposed SPH algorithm can be well applied in the prediction of the deformation and failure process of rock slope.